Optimisation of the Geometric Design Parameters of a Five Speed Gearbox for an Automotive Transmission - Bozca, M. (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
Optimisation of the geometric design parameters of a five speed gearbox for an automotive transmission is studied. The bending stress is considered as the objective function, and the design parameters are optimised under several constraints, including contact stress and constant distance between gear centres. During optimisation, the contact ratio changes with respect to pressure angle, and the effects of the contact ratio and profile modification on tooth bending stress are analysed. By optimising the geometric design parameters of a gearbox, including the module, number of teeth, helix angle and face width, it is possible to reduce tooth bending stress and obtain a light-weight-gearbox structures. It can be concluded that increasing the contact ratio results in a reduced tooth bending stress; however, in contrast, increasing the pressure angle caused a reduction in the contact ratio and an increase in tooth bending stress and contact stress. In addition, it can be concluded that positive profile modification reduces tooth bending stress. All of the geometric design parameters determined by optimisation satisfy all constraints.
Keywords: Gears; Contact ratio; Bending stress; Contact stress; Engineering